Transvesical Versus Posterior Approach to Retzius-Sparing Robot-Assisted Radical Prostatectomy: A Retrospective Comparison With a 12-Month Follow-Up - Deng, Wen; Zhang, Cheng; Jiang, Hao; Li, Yulei; Zhu, Ke; Liu, Xiaoqiang; Chen, Luyao; Liu, Weipeng; Guo, Ju; Zhou, Xiaochen; Fu, Bin; Wang, Gongxian (Frontiers in Oncology, 2021)
Objectives: To assess the perioperative, functional, and oncological outcomes of transvesical robot-assisted radical prostatectomy (T-RARP) and posterior robot-assisted radical prostatectomy (P-RARP) for localized prostate cancer. Materials and Methods: We analyzed the data of 96 patients who underwent T-RARP or P-RARP for localized prostate cancer between January 2017 and June 2019 in a retrospective fashion. Results: No significant differences in the baseline characteristics existed between the T-RARP and P-RARP arms. Both interventions were successfully performed without open conversion in either group. T-RARP was associated with a slightly more operative time (135.3 vs. 127.3 min) and estimated blood loss (105.2 vs. 94.2 mL) than P-RARP, but the differences were not significant (both p > 0.05). The likelihood of transfusion, ≤Grade II, and >Grade II postoperative complications, pT3a disease and positive surgical margins in the T-RARP group was comparable with that in the P-RARP group. No significant differences were noted between these two arms in terms of UC at the removal of catheter and nocturia (p = 0.750 and p = 0.684, respectively), and all included patients recovered UC at 3 months postoperatively. The median International Index of Erectile Function-5 score in both groups remains comparable before and after RARP. The patients in the T-RARP and P-RARP groups had a similar biochemical recurrence-free survival (p = 0.387). Conclusions: Both T-RARP and P-RARP by experienced hands are feasible for well-selected patients with prostate cancer, obtaining similar outcomes in terms of perioperative results, UC and erectile function, and oncological control within short-term follow-up.